Application of the Solving Methods and Numerical Differentiation for Curvature Parameter of Conjugate Surface - Zhou Weiguang; Wei Bingyang; Ouyang Hongfei; Wei Yihao (Jixie chuandong)
It is a basic problem to solve the principal curvature and direction of conjugate surface. Aiming at the complex and complicated problem of the conventional method to solve the principal direction and the principal curvature of conjugate tooth surface,a kind of calculation method to solve problem based on numerical differentiation is proposed. The meshing coordinate system is established and the conjugate tooth surface equations are deduced,with a pair of space staggered shaft drive hypoid gear as the research object. The calculation of principal curvatures and directions of conjugate surface of pinion is carried out. The advantages and disadvantages of common methods of numerical differential method,LITVIN method and the method of induced curvature are compared and analyzed. It is shown that the numerical differential method is clear and easy to be used in calculating by the computer,and this result is precise.